Argon Laser in Human Tympanoplasty - Escudero, Luiz H. (1979)
We describe the use of an argon laser in human tympanoplasty. The laser was used in two different ways: (1) to stop the bleeding of small vessels in the external auditory channel and eardrum remains; and (2) to spot-weld the new eardrum graft in the proper position. Seven operations were performed. We report the results.